“Коза”: проблема інтерпретації обрядової гри в етнографічній літературі - Гуменюк, П. (Народна творчість та етнографія, 2005)
In the scientific researches of the recent years we often meet the description and the analysis of the “goat” image in the context of the Christmas Rites and Rituals. But a lot of empirical materials prove that this image appears in the spring calendar cycle as well. We are going to try to separate all the occasions under which “goat” appears in the folk rituals, rites and texts. According to traditional classification we have following occasions: folk games, New Year Rites, Christmas play. Through the detailed description of all these rites and their meaning and symbolism we are trying to point out the origins of this image in various folk forms and to point out that it is important to learn more about its appearance in spring calendar rituals and rites which was not studied deeply enough before. The comparative analyses of two calendar cycles (winter and spring) might help to found out more about “goat” image and its role in various folk traditions.